Pemanfaatan Batu Bara Muda Dan Kulit Kacang Tanah Menjadi Briket Oleh Kelompok Penerima Manfaat Program Keluarga Harapan (PKH) - Samsul Fajri; Miftahul Rizky; Ersa Rana; Supardi; Muhammad Hasim S; Aminuddin; Baso Riadi Husda (Vokatek: Jurnal Pengabdian Masyarakat, 2023)
The community service activities carried out by the FT team at Universitas Negeri Makassar which were carried out in Lanne Village, Tondong Talasa District, Pangkep Regency, have made a very significant contribution to the community, especially in the Lanne village area, we received great appreciation. good reception and high enthusiasm. The briquette making training held in Lanne Village is one way to make use of peanut shells that are simply thrown away or become trash. This training is expected to improve the community's economy and reduce the use of LPG. Some of the supporting factors for this activity include: Training participants have a great willingness to obtain information and knowledge about briquette making. By utilizing peanut shells which are usually thrown away because the people of Lanne Village are mostly peanut farmers and it's good that young coal is easy to get there, once a former coal mine has now become a former mine. The obstacles experienced during the activity were damaged roads so it took quite a long time to get to the training location quickly.